Pelvic floor muscles training to reduce symptoms and signs of vulvovaginal atrophy: a case study. Issue 7 (July 2016) - Mercier, Joanie; Morin, Mélanie; Lemieux, Marie-Claude; Reichetzer, Barbara; Khalifé, Samir; Dumoulin, Chantale
Abstract: Objective: Vulvovaginal atrophy (VVA), caused by decreased levels of estrogen, is a common problem in aging women. Main symptoms of VVA are vaginal dryness and dyspareunia. First-line treatment consists of the application of local estrogen therapy (ET) or vaginal moisturizer. In some cases however, symptoms and signs persist despite those interventions. This case study describes a 77-year-old woman with severe VVA symptoms despite use of local ET and the addition of pelvic floor muscle (PFM) training to her treatment. Methods: A patient with stress urinary incontinence and VVA was referred to a randomized clinical trial on PFM training. On pretreatment evaluation while on local ET, she showed VVA symptoms on the ICIQ Vaginal Symptoms questionnaire and the ICIQ-Female Sexual Matters associated with lower urinary tract Symptoms questionnaire, and also showed VVA signs during the physical and dynamometric evaluation of the PFM. She was treated with a 12-week PFM training program. Results: The patient reported a reduction in vaginal dryness and dyspareunia symptoms, as well as a better quality of sexual life after 12 weeks of PFM training. On posttreatment physical evaluation, the PFMs' tone and elasticity were improved, although some other VVA signs remained unchanged. Conclusions: Pelvic floor muscle training may improve some VVA symptoms and signs in women taking local ET. Further study is needed to investigate and confirm the present case findings and to explore mechanisms of action of this intervention for VVA.